Perancangan Media Pembelajaran Interaktif Pengenalan Isyarat Huruf Hijaiyah untuk Siswa Disabilitas Rungu SLBN Sukapura Bandung - Hamidah, Azmi Fauziah; Hilmi, Muhammad Irfan; Prasetyani, Ananda; Mutiaz, Intan Rizky (Universitas Komputer Indonesia, 2025)
This study aims to design an interactive learning medium as a tool for introducing sign-based Hijaiyah letters to students with hearing disabilities at SLB Negeri Sukapura. Hearing-impaired students often face challenges in understanding orally and auditorily delivered material. Therefore, there is a need for more inclusive and visually oriented media. The development of this learning medium employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. Data obtained from this study—based on content, programming, and visual aspects—shows that the seven participating students gave an average score of 91%, categorized as “Excellent.” The classroom teacher’s evaluation also resulted in a 92% score, likewise categorized as “Excellent.” Based on these results, the learning medium is deemed suitable for use.